China's Global Introspection: Managing Critical Thinking. (1st November 2019) - Williams, Austin
Abstract: Austin Williams, architect, course leader at London's Kingston University and expert correspondent on contemporary China's architecture scene, presents a brief vignette of architectural culture behind the Chinese firewall and the particular issues that affect it.